Effect of switching from tenofovir disoproxil fumarate to tenofovir alafenamide on estimated glomerular filtration rate slope in patients with HIV: A retrospective observational study. Issue 3 (March 2022) - Hikasa, Shinichi; Shimabukuro, Shota; Hideta, Kyoko; Higasa, Satoshi; Sawada, Akihiro; Tokugawa, Tazuko; Tanaka, Kuniyoshi; Yanai, Mina; Kimura, Takeshi
Abstract: Introduction: There is limited data on the effects of switching from tenofovir disoproxil fumarate (TDF) to tenofovir alafenamide (TAF) on estimated glomerular filtration rates (eGFR) slope in patients with human immunodeficiency virus (HIV) infection. This study aimed to compare the eGFR slope when administering TDF and TAF and to investigate the predictors of improvement in eGFR slope after switching from TDF to TAF. Methods: We conducted a single-center, retrospective, observational study in Japanese patients with HIV infection who switched the antiretroviral drug from TDF to TAF. eGFR was calculated using serum cystatin C. The eGFR slope was defined as the regression coefficient between eGFR and time. Differences between eGFR slope during TDF and TAF administration were compared using Wilcoxon signed rank test. A stepwise logistic regression model was used to examine the associations between improvement of eGFR slope after switching from TDF to TAF and various parameters. Results: Overall, 63 patients (656 eGFR) were included in the analysis. The median analyzed durations of TDF and TAF exposures were 1.6 and 1.5 years, respectively. There were no significant differences between eGFR slope during TDF and TAF periods (median: 0.6 vs. 4.0 mL/min/1.73 m 2 /year, p = 0.165). The eGFR slopes during the TDF period and while switching from TDF to TAF were independent predictors of improvement in eGFR slope after switching from TDF to TAF. Conclusions: The results suggest that patients with poor renal function and those with progressive worsening during TDF administration would benefit from switching to TAF.